Modeling Conductive Heat Flow Between Steep Rock Walls and Talus Slopes – Thermal Processes and Geomorphological Implications - Myhra, Kristin Sæterdal; Westermann, Sebastian; Etzelmüller, Bernd (Frontiers in Earth Science, 2019)
The thermal regime in steep and snow-free rock slopes is crucial for understanding rock slope stability, frost weathering and the associated material production in steep mountain areas. In this study, we model heat flow and explore the hypothesis that strong thermal gradients are maintained in transition areas between snow-free rock walls and snow-covered talus slopes. The results of our 2D heat transfer modelling experiments indicate that, under the assumption of snow-free steep rock walls, conductive heat flow can cool the upper parts of an adjacent talus slope with low conductivity and induce strong thermal gradients in the solid bedrock. The modelled conductive cooling effect may be relevant for both frost weathering processes and subsequent geomorphological implications and for the thermal regime of complex surface material in rock wall-talus systems in alpine areas.